(untitled) (Diyala Journal of Engineering Sciences, 2023)
Chemical stabilization of soil is essential for construction work because it improves engineering characteristics of soil, such as swelling soil stability. The main objective of the research is to investigate the impact of adding Metakaoline (MK) on the behavior of expansive soil to reduce swelling. Different amounts of Metakaoline, such as 2 %, 4 %, and 6 % of the weight of dry soil, are used to prepare the soil specimens. The engineering properties of the soil sample are examined using a variety of laboratory tests (consolidation, swelling potential, and liner shrinkage) original and treated soil at various mixing ratios to determine the swell potential and swelling pressure. The findings showed that the addition of MK has caused a reduction in the swelling reaching about 91% with 4% MK at 14 days, Also, the swelling pressure decreased from 110 kPa to 30 kPa with 4% Metakaolin.